Privacy matters. - Greengard, Samuel (Communications of the ACM, 2008)
The article discusses the protection of personal data and information, examining ways that computer scientists and others are attempting to use a concept called "differential privacy" to standardize the manner in which personal data is protected. The way in which computer hackers can cull through unrelated data from unrelated sources and create a profile of someone is called a linkage attack. Other topics include combining released statistics,introducing random noise, and databases that behave the same.